Emerging muscle abnormalities in the Pectoralis major muscle of broilers – review (Research, Society and Development, 2020)
The objective of this literature review was to address the qualitative characteristics of meat, chemical and morphological muscle fibers of the main myopathies (deep pectoral myopathy - MPP, white striping - WS, wooden breast -WB and spaghetti meat - SM) verified in the slaughter line broilers in recent years. The occurrence of these abnormalities in the breast muscle (Pectoralis major), coupled with the accelerated growth rate and high breast yield, is an emerging concern for the poultry industry and the demand for strategies that make the production system feasible to mitigate economic losses from convictions of the carcasses or from the rejection of consumers. Therefore, the main challenge is to reduce the occurrence of these muscle lesions but without harming the productive and qualitative indexes of the meat, considering that it is one of the main causes that decrease the quality of the breast meat with the potential to impact the choice of the final consumer.